Institutional Structure and Program Choices in Television Markets - Beebe, Jack H. (Quarterly Journal of Economics, 1977)
Introduction, 15.—The welfare criterion, 16.—Assumptions, 18.—Calculating program patterns, 21.—Counterexamples to Steiner's result, 23.—Ownership structure, channel capacity, and program patterns, 26.—Consumer surplus and total surplus, 31.—Welfare conclusions and policy implications, 35.